Visually exploring fungi through a pattern-based lens - Garelle-Essam, Mila, author (Colorado State University. Libraries, 2024)
This honors thesis explores the value of art and visual pattern specifically for communicating and transforming science to better understand the world around us. Our current reality is a world where humans and science commonly perceive a paternalistic separation from all other living beings. Luckily, people recognize their inherent connection and curiosity for nature when they see intricate beauty found in all of life. Including humanities like emotion and culture in scientific realms helps us see science as storytelling and engages students to ask deeper questions. In this project I tell the story of my efforts to capture microscopic mycelial growth using time-lapse photography. This project culminates in a 4-minute film that focuses on the patterns expressed by the fungal kingdom at a variety of time and size scales. The film is guided by a meditative poem allowing the patterns of life to fill the viewers mind and inspire connection. The film is linked at the beginning of the reflection paper.